Komunikasi Interpersonal Orang Tua Pengguna Facebook dalam Memotivasi Prestasi Anak di Desa Sedinginan - Maulina, Dinanda; Aslinda, Cutra (Journal of Social Media and Message, 2022)
The purpose of this study is to find out and analyze the Interpersonal Communication of Facebook Users' Parents in Motivating Children to Achieve Achievements in Sedinginan Village, Rokan Hilir Regency. In this study, the problem that the authors put forward is how the interpersonal communication of parents of Facebook users in motivating children to achieve achievements in Sedinginan Village, Rokan Hilir Regency. This study uses qualitative research, and collects data using interviews, observation, and documentation directly to the sample in the study, namely 5 families in Sedinginan village. The results in this study indicate that: the interpersonal communication process that occurs between parents of Facebook users and their children in Sedinginan Village, Rokan Hilir Regency has not gone well, there is still a gap between parents of Facebook users and their children caused by excessive use of Facebook social media. , as well as creating distance between parents of Facebook users and their children.